Rosie's walk / Pat Hutchins - Hutchins, Pat (New York, Macmillan, 1968)
Although unaware that a fox is after her as she takes a walk around the farmyard, Rosie the hen still manages to lead him into one accident after another.
Keywords: Chickens; Picture books